Dynamic pricing‐based integration for non‐cooperative ubiquitous sensing and communication network - Ren, Chao; Dai, Weiheng; Gong, Chao; Li, Haojin; Sun, Chen; Lu, Yang (Electronics letters, 2024)
As 5G and early‐stage network technologies mature, a wealth of data and experience is accumulated. The ubiquitous sensing and communication network (USCN) can leverage these existing communication infrastructures to maximize resource utilization and reduce the costs of redeployment through integration with modern 6G and beyond 6G networks. However, implementing future integrated sensing and communication (ISAC) functions in USCN may possess different hardware capabilities and communication protocols, presenting significant challenges. This is due to the lack of a unified framework for managing and optimizing these heterogeneous resources, as well as the absence of reasonable performance metrics. This letter proposes a dynamic pricing coordinated resource allocation (DPCRA) mechanism to realize the emerging ISAC in legacy USCNs. The DPCRA is designed to optimize the spectrum efficiency (SE) of USCN and manages resource interactions between heterogeneous devices through price variables, thereby resolving resource conflicts and deadlocks. The novelties include: (1) employing a price mechanism to foster resource cooperation in non‐cooperative networks; (2) introducing an SE metric incorporating an information similarity factor for optimization; (3) dynamically selecting resources to enhance SE. Simulations demonstrate that the DPCRA effectively resolves device deadlock while maintaining high SE levels, promoting device collaboration. This letter presents a ubiquitous sensing and communication network framework that integrates integrated sensing and communication (ISAC) systems into existing networks to enhance efficiency and reduce costs. It introduces the dynamic pricing coordinated resource allocation (DPCRA) algorithm for optimal resource management, which dynamically allocates resources to coordinate sensing and communication functions effectively. The algorithm addresses resource contention and deadlocks, promoting device collaboration and sustaining high spectral efficiency. Simulation results demonstrate the DPCRA method's superiority in spectral efficiency and its potential to advance ISAC.